2012
DOI: 10.1111/j.1440-1746.2012.07227.x
|View full text |Cite
|
Sign up to set email alerts
|

N‐3 polyunsaturated fatty acid attenuates cholesterol gallstones by suppressing mucin production with a high cholesterol diet in mice

Abstract: N-3PUFA attenuated gallstone formation in mouse, through increasing the levels of bile phospholipids and suppressing bile mucin formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 16 publications
(14 reference statements)
0
23
0
Order By: Relevance
“…ursodeoxycholic) acids, and thus, the final hydrophobicity of the bile salts depends on the relative contents of these components [55][56][57]. Therefore, the biliary bile salt composition affects human gallstone formation, which opens several therapeutic possibilities [58][59][60][61]. Our results showed that there were no significant differences between the two groups of patients in the mean concentrations of total bile acids, phospholipids, or cholesterol in vesicular bile, except for the lower mean concentrations of glycocholic and taurocholic acid in the patient group.…”
Section: Discussionmentioning
confidence: 99%
“…ursodeoxycholic) acids, and thus, the final hydrophobicity of the bile salts depends on the relative contents of these components [55][56][57]. Therefore, the biliary bile salt composition affects human gallstone formation, which opens several therapeutic possibilities [58][59][60][61]. Our results showed that there were no significant differences between the two groups of patients in the mean concentrations of total bile acids, phospholipids, or cholesterol in vesicular bile, except for the lower mean concentrations of glycocholic and taurocholic acid in the patient group.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, animals eating a diet that contains polyunsaturated fat, such as fish oil, have a lower incidence of CGS than those eating a diet that contains saturated fat (Kim et al 2012). It is known that fiber-rich diets are beneficial in preventing the formation of CGS.…”
Section: Introductionmentioning
confidence: 98%
“…In fact, in an experimental model with mice, N-3 polyunsaturated fatty acid reduces cholesterol gallstones formation by suppressing the mucin production and the MUC2, MUC5AC, MUC5B and MUC 6 mRNA expression levels. 4 The protective efficacy of omega-3 fatty acid on cholesterol gallstones formation in human could be proven by the lower incidence of gallstones formation in the Canadian Eskimo (that have a genetic predisposition to the metabolic epidemic syndrome and to form cholesterol gallstones, because of they are direct relate to Native Americans or Paleo-Indians 5 ) when they follow a fish-rich diet; on the contrary, cholesterol gallstones incidence among these tribes rapidly groove when they follow a westernized-type diet (cholesterol and omega-6 rich/omega-3 poor). 4 This effect could be tested in adult patients with metabolic epidemic syndrome (that usually are also affected by cardiovascular diseases and hypertension) adding oral omega-3 fatty acid to Statins or Ezetimibe plus Aspirin 3 ; the final result could be a reduction in the incidence of symptomatic cholesterol gallstones disease that require hospitalization and, sometimes, a surgical treatment.…”
mentioning
confidence: 97%